Загрязнение территорий промышленных городов цинком и другими тяжелыми металлами - Бувалец, Дарья Юрьевна; Капустин, Алексей Евгеньевич (НТУ "ХПИ", 2015)
На примере г. Мариуполь рассмотрено загрязнение тяжелыми металлами городских почв, речных вод и донных отложений в условиях влияния предприятий черной металлургии. Проведенные исследования позволили установить степень и характер загрязнения территории г. Мариуполь различными тяжелыми металлами. Было выяснено, что загрязнение хромом, медью и никелем носит характер очагов, локализованных вблизи металлургических предприятий. В то время как загрязнение цинком и свинцом носит повсеместный характер. Полученные результаты могут быть использованы для дальнейшего мониторинга загрязнения города тяжелыми металлами и разработки мер повышения экологической безопасности.

Heavy metal pollution of cities is an urgent environmental problem. As an example we took Mariupol, on the territory of this city there are two large metallurgical plants. We have studied the heavy metal pollution of urban soils, river water and sediment, which are under the influence of the steel industry. Studies have established the degree and nature of pollution of the Mariupol by various heavy metals. Also, study revealed excess of some heavy metals in the river waters and sediments. We found out that the pollution of chromium, copper and nickel has the character of areas, localized near the metallurgical plants. It was estab-lished that the main source of pollution by these metals are coarse dust emissions. Whereas zinc and lead contamination is observed in all city territory. Based on analyzes of metallurgical emission, it was found that the main source of zinc and lead are the atmospheric emissions of fine dust. Study of soil pollution with heavy metals in Mariupol and determination of the impact of the steel industry was carried out for the first time. The results can be used for further monitoring of pollution of the city with heavy metals and the development of measures to improve the environ-mental security.
Heavy metal pollution of industrial cities
Keywords: загрязнение территорий; почва; металлургические отходы; экологическая безопасность; heavy metals; soil pollution; metallurgical waste; environmental safety